Influence of Maternal Age on Obstetric Outcome in Turkish Women - Pembe Keskinoğlu; Metin Pıçakcıefe; Nurcan Bilgiç; Hatice Giray; Nuriye Karakuş; Türkan Günay (Medical Network, 2007)
OBJECTİVE: The aim of this study was to assess the influence of maternal age on obstetric outcomes in women aged 35 years and older. STUDY DESIGN: This retrospective and descriptive study was performed by analysis of patient's files at a maternity hospital. The population of the study were 522 women aged ≥ 35 years who gave birth. Chi-square and t-test were used for statistical analysis. RESULTS: The prevalence of delayed childbearing was 6.5%. The most common obstetric complications were anemia, pregnancy-induced hypertension, and diabetes mellitus. The rates of preterm birth and low birthweight were 18.5%, 15.9%, respectively. The rate of neonatal complications in pregnant women aged 40 years and older was significantly higher than 35-39 years (52% and 43.6%, respectively) (p < 0.007). In pregnant women aged ≥ 35 years the rates of preterm delivery, cesarean section and operative delivery were found significantly higher compared with control group of 20-34 years. CONCLUSION: Obstetric and neonatal complications increased with age.